Organizational and psychological features of successful democratic enterprises: A systematic review of qualitative research - Christine Unterrainer; Wolfgang G. Weber; Thomas Höge; Severin Hornung (Frontiers in Psychology, 2022)
In organizational psychology the positive effects of democratically structured enterprises on their employees are well documented. However, the longstanding viability as well as economic success of democratic enterprises in a capitalistic market environment has long been contested. For instance, this has given rise to widespread endorsement of the “degeneration thesis” and the so-called “iron law of oligarchy”. By reviewing 77 qualitative studies that examined 83 democratic enterprises (including 15 studies on nine enterprises of the Mondragon Cooperative Cooperation network) within the last 50 years, the present systematic review provides evidence that such enterprises are able to economically survive and prosper. The majority of studied enterprises (63.5%) either resisted pressures toward degeneration or subsequently regenerated after undergoing degenerative processes. Only 9.5% fully degenerated in accordance with the degeneration thesis and the “iron law of oligarchy”, while 27.0% of the democratic enterprises showed diverse and mixed forms of degeneration tendencies, indicating that the notion of an “iron law” needs to be revised. Within the nine investigated cases of Mondragon not one single enterprise or group fully degenerated. Three cases showed degenerative tendencies, another three one degeneration tendencies and simultaneously regeneration, one case fully resisted degeneration tendencies (retention) and two cases regenerated. Further, this systematic review provides an overview of organizational and external conditions, non-/democratic or non-/participative practices and psychological phenomena that contribute to the degeneration, regeneration, or resistance to degeneration (i.e., retention). The described examples of such practices may help practitioners to implement and maintain democratic structures and processes in contemporary organizations.